(3GdCbhGd GdJaSjQjI aj eYLe GdeMce hGdeMjW GdCYXe dGHf SjOg GdeJhai SfI (B458(3g` ef Chd MQa GdYjf hMJi MQa GdcGa (B:s (3OQGSI fbOj`I (B/s - (3,eUWai eMeO eUWai eMeO ESeGYjds; (3eMeO bGSe GdefSjs (2024)
(3JJdNU QSGdI (B: (3GdCbhGd GdJaSjQjI aj eYLe GdeMce hGdeMjW GdCYXe dGHf SjOg GdeJhai SfI (B458(3g` ef Chd MQa GdYjf hMJi MQa GdcGa `` OQGSI fbOj`I ajeG jdj(B: (3GdQSGdI aj bSe GdJaSjQ hgj JYJeO Ydi GdOQGSI GdfbOjI aj eYLe GdeMce hGdeMjW GdCYXe dGHf SjOg, hJbhe GdQSGdI Ydi GSJNQGL GdGbhGd GdJaSjQjI, hBQGA GdeaSQjf ef eYLe GdeMce hGdeMjW GdCYXe, hebGQfJgG HGdeYGLe GdCNQi dZhjG, hebGQfJgG HCTgQ cJH GdJaSjQ, cJaSjQ GdWHQj hGdbQWHj hGHf cKjQ hZjQge, hJgJe HYQV BQGA GHf SjOg Ydi cHGQ GdeaSQjf, hEXgGQ eGhGab ajgG CTgQ GdeaSQjf heG NGda, eY fbO GdCbhGd, hGSJNQGL GdCbhGd GdeCKhQI ef CegGJ cJH GdJaSjQ hGddZI hZjQge, hJJchf GdQSGdI ef ebOeI hJegjO hCQHYI aUhd hNGJeI(B.s
The message is in the interpretation section and it depends on the critical study of the Mu'jam al-Muhkam and al-Muhit al-A'zam of Ibn Sidah. It depends on extracting the interpretive sayings from the Mu'jam al-Muhkam and al-Muhit al-A'zam dictionary and comparing them with other dictionaries linguistically and presenting Ibn Sidah's opinions to the great interpreters and showing what the most famous interpreters agreed with and what disagreed with the criticism of the sayings and extracting the famous sayings. The message consists of an introduction, a preface, four chapters and a conclusion
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B287-304.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdeaSQhfs -- (3JQGLes; (3GdTQjYI GdGSdGejIs; (3GdGbhGd GdJaSjQjI aj GdeMce hGdeMjW GdCYXes